Polyherbal formulations with optimum antioxidant properties - Abdul Rahim, Nur Fazira; Muhammad, Norhayati; Abdullah, Norazlin; A. Talip, Balkis; Dusuki, Nur Jihan Shahirah (2018)
The objective of this study is to determine the optimum antioxidant properties of polyherbal formulations of the aqueous extract of leaves of Strobilanthes crispus (pecah beling), Phyllanthus niruri (dukung anak), Orthosiphon aristatus (misai kucing) and Stevia rebudiana using in vitro method. There are 22 formulations consisting various proportions of the extracts designated using commercial statistical software package that is Design Expert 6.0.4. The antioxidant study of the individual extracts and their different combinations were conducted using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, Ferric Reduction Antioxidant Potential Assay (FRAP) and total phenolic content (TPC) assay. Results showed that O. aristatus has higher antioxidant properties in most of the assay when tested individually, as compared to S. crispus, P. niruri and S. rebudiana. Synergistic effect was exhibited in most of the polyherbal combinations. From the optimization process, it was revealed that the quadratic model was statistically significant for the FRAP and TPC while special cubic model was statistically significant for DPPH. The optimum mixture found for antioxidant properties was the polyherbal formulation that contain the extract of 23.96% of S. crispus, 0.62% of P. niruri and 75.42% of O. aristatus with desirability of 0.985. In conclusion, the results indicated that the formulations obtained in this present study justify the promising antioxidant properties of the polyherbal mixtures. Thus, it is sensible to use the combination of studied herbal formulation for development of any antioxidant supplement or food products in the future.